Jeerasannidhi Award Lecture - VA-Mycorrhiza - Dimensions of its application - CHANDRA, SUDHIR (Indian Phytopathology, 2002)
Mushrooms were known to mankind since the early phase of civilization but the German botanist Frank (1885) was the first to coin the term ’Mycorrhiza’ for designating a symbiotic relationship between fungi and plant roots. Initially his contention that the mycorrhiza represents a beneficial symbiosis between trees and fungus was challenged by his contemporaries but later researches during the first half of the present century established that the mycorrhizal colonization is responsible for increased growth and nutrient uptake in the forest trees. A great bulk of information regarding mycorrhiza accumulated during later period and it became known that many other types of mycorrhiza are of common occurrence in nature. Scientists started exploiting them for the welfare of the human beings. Many ways were devised to use them as tools for improving the productivity in plants or making them resistant against the vagaries of nature or pathogens.